Bioinspired Composite Hydrogels with Osteogenic, Angiogenic, and Antioxidant Properties for Enhanced Bone Repair - Guanghui Gu; Youyin Xu; Peng He; Chenxu Li; Shuqing Chen; Gang Wei; Yongming Xi (Small Structures)
The increasing demand of advanced biomedical materials for bone repair and regeneration has spurred significant research in recent years. While traditional hydrogels offer promising biocompatibility and easy fabrication, their application in bone reconstruction is often impeded by inadequate structural integrity and biological functions. Graphene oxide (GO) has emerged as a transformative additive, renowned for its exceptional mechanical and chemical properties, as well as its ability to enhance the structural integrity of hydrogels. In this study, the incorporation of GO into chitosan (CS) hydrogels is investigated, achieving bioinspired hydrogels with enhanced mechanical strength and stability, which are crucial for supporting bone regeneration. Additionally, self‐assembled synthetic peptide nanofibers (PNFs) are employed to enhance biocompatibility and facilitate biomimetic mineralization of the bioinspired hydrogels, a critical process for effective bone remodeling. This innovative composite hydrogel not only achieves biomimetic mineralization but also exhibits osteogenic, pro‐angiogenic, and antioxidant properties essential for bone repair. This novel method takes advantage of the distinctive properties of GO, PNFs, and biomass hydrogels, providing a robust and effective material solution with the potential to significantly advance the field of bone tissue engineering.